Synthesis of magnetic carbon nanotube material through ball-milling for carbamazepine removal from water: A feasible and reliable method - Shuangxi Zhou; Huiming Qi; Mingchao Zhang; Ayiguli Maimaiti; Zuozheng Ma; Hao Wu; Deyan Li; Wei Wang (Environmental Chemistry and Ecotoxicology, 2025)
Non recyclability of carbon nanotube materials (CNTs) has restrained their application in environmental field. Compared to chemical deposition，the ball-milling was a simple and cost-effective method to prepare magnetic CNTs for water treatment application. Various magnetic CNTs were prepared with different CNTs (outer diameters of 4–8 nm (CNT4) and 8–15 nm (CNT8)) and nano-Fe3O4 for carbamazepine (CBZ) removal from water. Prepared materials were characterized by various surface analyzing methods. Adsorption kinetics and isotherms, the effect of solution pH, co-existing ions, humic acid on CBZ adsorption, and regeneration experiments were carried out. According to the Langmuir model, the maximum adsorption capacity of prepared MCNT4–5 (177.80 mg/g) was similar to CNT4 (174.62 mg/g), and an obvious enhancement of MCNT8–7 (81.87 mg/g) compared to CNT8 (54.60 mg/g). Notably, introducing nano-Fe3O4 (low capacity for CBZ) caused the mass loss of adsorbents (CNTs), which might be compensated by the ball-milling process, increasing the proportion of micro- or meso- pores of prepared magnetic CNTs. Meanwhile, the treatment of ball-milling (CNTs and nano-Fe3O4) lead to more O-structure and aromatic structure exposed on the surface of magnetic materials, thus promoting the adsorption capacity of MCNT4–5 as evidenced by XPS spectrum. Furthermore, MCNT4–5 showed excellent reusability with stable removal percentage (> 86 %) within 10 cycles. Results indicate that ball-milling is a processing technique to achieve high recyclability, environmental friendliness, and cost-effectiveness materials, which is expected to enhance the application of nanomaterials in water purification field.